The Use of Navigation Forces for Assessment of Wrist Arthroscopy Skills Level - Obdeijn, Miryam C.; van Baalen, Sophie J.; Horeman, Tim; Liverneaux, Philippe; Tuijthof, Gabrielle J. M. (Journal of Wrist Surgery, 2014)
Purpose To provide an efficient learning process, feedback on performance is crucial. In skills laboratories, it is possible to measure the skills and progression of skills of the trainees objectively. This requires metrics that represent the learning curve of the trainee, which were investigated for wrist arthroscopy. The research questions were: Methods A cadaver wrist was mounted in a custom-made distraction device mounted in front of a force platform (ForceTrap). Eleven novices were invited to perform two tasks on the wrist: The second task was repeated 10 times. The absolute force (Fabs) and the direction of force were measured. The angle α is defined in the vertical plane, and the angle β in the horizontal plane.Results The median Fabs used by novices remained below the force threshold as defined from the expert data (7.3 N). However, the direction of the applied forces by novices in both planes was not consistent with expert data and showed a wider range. Also, there was no improvement after more trials.Conclusion Our study suggests by the absence of a learning curve for the novices and a significant difference between novices and experts that novices can benefit from feedback on the magnitude and direction of forces to improve their performance.
Keywords: arthroscopy wrist; education; forces; learning; navigation